EFFICIENT EXPLOITATION OF LAND IN AGRICULTURE - Bahodirjon Nosirov; Dilobar Fakhritdinova (Galaxy International Interdisciplinary Research Journal, 2023)
Nowadays, the agriculture is one of main sectors of the Uzbekistan economy. Arrive, hot sun, millions of experienced laborers, tall request for Uzbek natural products and vegetables with unique taste, and the nearness of huge markets close us make the require for little ranches in thickly populated ranges with tall unemployment. Creation of little ranches within the field of natural product and vegetable generation requires the redistribution of the farmers’ lands within the area where they are as of now operating. However, for the foremost portion, those who don’t right now have coordinate family individuals are cleared out with a cultivate proprietor who, rather than a family part, employments his claim labor constrain instead of his possess. The other portion will be given to those who have a tall level of cultivating encounter.